Seeking Allah, finding Jesus: a devout Muslim encounters Christianity - Qureshi, Nabeel (Zondervan Reflective, 2018)
Qureshi describes his dramatic journey from Islam to Christianity, and shares how he developed a passion for Islam before discovering, almost against his will, evidence that Jesus rose from the dead and claimed to be God-- and of the peace he eventually found in Jesus